A comparison of alfalfa and alfalfa plus grain for wintering heifer calves on bluestem - Smith, E.F.; Koch, B.A.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
Twenty-two head of good quality Hereford heifer calves purchased from the Harris Ranch at Melrose, New Mexico, were used in the test. They were divided on the basis of weight into two lots of 11 heifers each and wintered on bluestem pasture with the following treatments: Pasture 8-Fed 4 pounds of alfalfa hay and 2.5 pounds of corn per head daily. Pasture 13-Fed 8 pounds of alfalfa hay per head daily. The 2.5 pounds of corn fed to pasture 8 furnished approximately the same amount of total digestible nutrients as the additional 4 pounds of alfalfa bay fed to pasture 13. Plenty of grass was available in both pastures. The heifers had free access to salt.
Keywords: Beef; Alfalfa; Bluestem pasture; Grain